A systematic review and meta‐analysis of the effectiveness of meal replacements for weight loss. (24th January 2019) - Astbury, Nerys M.; Piernas, Carmen; Hartmann‐Boyce, Jamie; Lapworth, Sophia; Aveyard, Paul; Jebb, Susan A.
Summary: Meal replacements (MR) are generally not recommended in clinical guidelines for the management of obesity. The aim of this review is to provide an up‐to‐date systematic evaluation of the effect of weight loss interventions incorporating MR compared with alternative interventions on weight change at 1 year in adults with overweight or obesity. Six electronic databases were searched from inception to the end of August 2018 for randomized controlled trials comparing the effect of MR with interventions that did not include MR on weight at 1 year. We excluded studies using diets providing <3347 kJ/(800 kcal)/day and those which used total diet replacement (TDR) from this review. Risk of bias was assessed using the Cochrane risk of bias tool. Twenty‐three studies with 7884 adult participants were included. Six out of 23 studies were judged at low risk of bias across all domains, and 5/23 studies were judged at high risk of bias in at least one domain. Studies with similar intervention and comparators were grouped into five comparisons for analysis. Mean weight change at 1 year favoured the MR group relative to the control group in each comparison. In those comparisons where we conducted meta‐analysis, in people assigned to a diet incorporating MR, mean difference was −1.44 kg (−2.48 to −0.39 kg; I 2  = 38%) compared with alternative kinds of diets. In those assigned to a MR diet along with support, mean difference was −2.22 kg (−3.99 to −0.45, I 2  = 81%) compared with other diets with support and −3.87 kg (−7.34 to −0.40; I 2  = 60%) compared with other kinds of diet without support. In those assigned a MR diet with an enhanced level of support, mean difference was −6.13 kg (−7.35 to −4.91, I 2  = 19%) compared with alternative diets and regular support. Programmes incorporating meal replacements led to greater weight loss at 1 year than comparator weight loss programmes and should be considered as a valid option for management of overweight and obesity in community and health care settings.